The Chemistry and Pharmacology of Genistein - Fatima, Atiya; Singh, Ram (Natural Products Journal, The, 2016)
Genistein is a natural compound belonging to the chemical class of isoflavone. This molecule is present in the significant portion of our diet in the form of Soy food products. This is the most extensively studied isoflavone due to its significance affinity towards targets of potential pharmacological and neutraceutical benefits. The potential pharmacological applications of this molecule have been found as anti-cancer, anti-obesity, anti-diabetic, neuroprotective, antiosteoporosis, and cardio protective agent. This review provides comprehensive coverage of the chemistry, pharmacology, toxicity and extraction of genistein.
Keywords: soy food